2022
DOI: 10.1093/europace/euac222
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous metaplasia prolongs repolarization and increases repolarization dispersion within post-infarct ventricular tachycardia circuit cites

Abstract: Aims Post-infarct myocardium contains viable corridors traversing scar or lipomatous metaplasia (LM). Ventricular tachycardia (VT) circuitry has been separately reported to associate with corridors that traverse LM and with repolarization heterogeneity. We examined the association of corridor activation recovery interval (ARI) and ARI dispersion with surrounding tissue type. Methods and results The cohort included 33 post-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…3 We reported that, via registering the LGE-CMR images and the cardiac CECT images, 33% of LM detected from the cardiac CECT was located within the border zone, while 60% of LM was located within the dense LGE area. 31 Although LGE images are the gold standard for evaluating scar, 30 other CMR sequences or other modalities (eg, CT) are required to differentiate LM from scar or edema on LGE images. Segmentation of LGE images should be performed cautiously, because the bright EAT can obscure the subepicardial contour in the presence of subepicardial LGE and ventricular blood pool can obscure the subendocardial border in the presence of subendocardial LGE.…”
Section: Lm Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We reported that, via registering the LGE-CMR images and the cardiac CECT images, 33% of LM detected from the cardiac CECT was located within the border zone, while 60% of LM was located within the dense LGE area. 31 Although LGE images are the gold standard for evaluating scar, 30 other CMR sequences or other modalities (eg, CT) are required to differentiate LM from scar or edema on LGE images. Segmentation of LGE images should be performed cautiously, because the bright EAT can obscure the subepicardial contour in the presence of subepicardial LGE and ventricular blood pool can obscure the subendocardial border in the presence of subendocardial LGE.…”
Section: Lm Imagingmentioning
confidence: 99%
“…Using image to electroanatomic map registration, our group and others have reported the electrophysiological features of LM. LM exhibits significantly lower intracardiac electrogram voltage amplitude, 3,6 higher electrical impedance, 3 lower current amplitude, 3 prolonged repolarization time, increased regional repolarization variation, 31 and slower conduction velocity, 4,53 and subtantial colocolization with the deceleration zone 54 compared with scar 54 (Table S2). Therefore, LM appears to be a vital contributor to VT circuitry in patients with prior MI.…”
Section: Lm Imagingmentioning
confidence: 99%
“…Still, several clinical studies have shown that VT circuits are associated with repolarization heterogeneity. 3 , 8 , 9 Thus, targeting the regions exhibiting repolarization heterogeneities may represent a potential strategy to eliminate ventricular arrhythmia. 10 …”
mentioning
confidence: 99%
“…In this issue of Europace , Xu et al . 9 report on the relationship between fat deposition and ARIs in patients presenting with post-infarction VT. They further explore how these two parameters (one structural and one functional) relate to VT circuits, in a series of 33 patients referred for VT ablation with available pre-operative CMR and CT studies.…”
mentioning
confidence: 99%
“…Lipomatous metaplasia (LM) refers to the replacement of myocardial scar with adipose tissue, commonly following myocardial infarction (MI). 16 According to Ichikawa et al, 17 the volume of LM increases over time following an MI. Similarly, monomorphic VT in ischemic cardiomyopathy can occur years after an MI.…”
mentioning
confidence: 99%